2005
DOI: 10.1111/j.1467-842x.2005.tb00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of hepatitis C in HIV‐negative homosexual men in Sydney, Australia

Abstract: Objective: To determine the prevalence and risk factors for hepatitis C (HCV) in HIV-negative homosexual men in Sydney. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Overall, our results correspond well with previously published prevalence estimates from Sydney (Health in Men study), where 7 out of 824 HIV-negative men aged 18-75 years (0.85%) tested positive for HCV antibodies [42]. As in the Australian study, we found no associations between HCV seropositivity and sexual practices that could have plausibly facilitated blood exposure, such as UAI and fisting.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our results correspond well with previously published prevalence estimates from Sydney (Health in Men study), where 7 out of 824 HIV-negative men aged 18-75 years (0.85%) tested positive for HCV antibodies [42]. As in the Australian study, we found no associations between HCV seropositivity and sexual practices that could have plausibly facilitated blood exposure, such as UAI and fisting.…”
Section: Discussionsupporting
confidence: 91%
“…However, persons screened were HIV-negative MSM, a subpopulation almost unaffected by the current HCV outbreaks [29]. Moreover, HCV screening stopped before the onset of the HCV outbreaks reported in Europe.…”
Section: Discussionmentioning
confidence: 97%
“…Large longitudinal studies of HCV-serodiscordant heterosexual couples have not yielded significant evidence for sexual transmission; so condom use for the prevention of HCV transmission has not been recommended for vaginal intercourse between monogamous HCV-serodiscordant sexual partners [33][36]. Large cohort studies of HIV-negative MSM showed that sexual behaviour, including unprotected anal intercourse (UAI), was not associated with prevalent HCV infections [37]; and those HCV seroconversions rarely observed among MSM without HIV infection could typically be attributed to injection drug use [10], [38]. Certain sexual practices involving trauma of the rectal mucosa have been discussed as relevant risk factors among MSM [13], [39].…”
Section: Introductionmentioning
confidence: 99%